PERANCANGAN MESIN SERUT BAMBU UNTUK BAHAN BAKU KERTAS - Dermawan, Farit Aziz; Sulaksono, Bambang (Jurnal Vokasi Indonesia, 2020)
In the world, the development of the paper industry continues to increase, which is caused by increasing consumers and the high demand for raw material for paper production producers, namely wood as the main composition in making paper. The increasing use of paper so that the availability of wood, especially from forests is getting depleted and the price is getting more expensive, so paper producers are looking for solutions to reduce dependence on wood as a raw material composition in paper making, an alternative substitute for wood raw materials in producing paper, namely with non-wood raw materials, namely bamboo. Bamboo is considered easier to cultivate with a short growth rate and is easy to harvest, the bamboo chosen is the type of betung bamboo because Betung bamboo has fiber properties that are not hard, making it suitable for use as raw material for paper production, besides that the price is sufficient. affordable. In paper making, there are various stages, designers are interested in making detailed designs for bamboo shaved machines, to update the previous machines. This study aims to determine the effect of the blade design on bamboo shavings that occurs in the process of crushing bamboo stalks into small pieces, and to compare the output results of bamboo powder with the level of fineness of the two bamboo shavings. for the paper-making process there are various kinds of stages. The design begins using the Pahl and Beitz design method. Pahl and Beitz suggested that identification by means of interviews, so as to produce a selected variation design. Then proceed with detailed design, namely in the form of calculations of each component and end by conducting an analysis using the Inventor 2019 software. Specifications for the standard JIS G 450 bamboo drawstring machine, using a 5.3 HP AC electric motor with a rotation speed of 2400 Rpm, then continued using the shaft to transmit the transfer of power to the pulley and belt belt by producing movement of the blade and frame tools used, namely 50x50x5 mm size angle iron.